The effectiveness of policy communication in promoting #KangPisMan program among university students - Heni Nuraeni Zaenudin; Rika Sartika; Muhammad Endriski Agraenzopati Haryanegara (Informasi, 2021)
This study is aimed at measuring the effectiveness of policy communication in promoting #KangPisMan program among university students. #KangPisMan is a top priority program of Bandung Municipal Government to tackle waste management problem. In this sense, the problem of plastic waste has become a global concern about environment, therefore it is a hope that, by promoting #KangPisMan, a new lifestyle will make people more aware of environmental sustainability. The program was established in 2018, so it is necessary to measure the effectiveness of its communicating strategy. In terms of public communication, the realization of promoting the program should be measured based on its optimal value. The present study seeks to analyse the effectiveness of communication strategy by employing 7C concepts as introduced. The questionnaire was distributed to 300 respondents (based on purposive sampling) which were registered as students of Faculty of Social Sciences Education, Universitas Pendidikan Indonesia. Validity of the questionnaire is measured by corrected item-total correlation. The analysis shows that communication strategy in promoting #KangPisMan was relatively effective by considering the lowest scores of continuity and consistency. It shows that the aspect of consistency in promoting the program should be enhanced. Meanwhile, the aspect of credibility had the highest value. Therefore, it is a big capital to promote the program through the role model as reflected by the team. In general, all respondents were satisfied of the communication strategy in promoting the program. However, the effectiveness is still potential to be developed in the upcoming time.